2012
DOI: 10.2174/157340312803760721
|View full text |Cite
|
Sign up to set email alerts
|

Triggers and Anatomical Substrates in the Genesis and Perpetuation of Atrial Fibrillation

Abstract: The definition of atrial fibrillation (AF) as a functional electrical disorder does not reflect the significant underlying structural abnormalities. Atrial and Pulmonary Vein (PV) muscle sleeve microstructural remodeling is present, and establishes a vulnerable substrate for AF maintenance. In spite of an incomplete understanding of the anatomo-functional basis for AF, current evidence demonstrates that this arrhythmia usually requires a trigger for initiation and a vulnerable electrophysiological and/or anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 127 publications
0
45
0
2
Order By: Relevance
“…2 Presently, AF usually requires a trigger for initiation and a vulnerable electrophysiological and/or anatomical substrate for maintenance. 3 Allessie et al 4 reported that left atrial (LA) remodeling progressed in a series of electrical remodeling, subsequent contractile remodeling, and finally structural remodeling. Previous research indicated that LA electrophysiological disorders in AF were represented by low-voltage zones (LVZs) obtained by contact bipolar voltage mapping during sinus rhythm (SR) 5 and that LVZs correlated with local conduction delays.…”
Section: Introductionmentioning
confidence: 99%
“…2 Presently, AF usually requires a trigger for initiation and a vulnerable electrophysiological and/or anatomical substrate for maintenance. 3 Allessie et al 4 reported that left atrial (LA) remodeling progressed in a series of electrical remodeling, subsequent contractile remodeling, and finally structural remodeling. Previous research indicated that LA electrophysiological disorders in AF were represented by low-voltage zones (LVZs) obtained by contact bipolar voltage mapping during sinus rhythm (SR) 5 and that LVZs correlated with local conduction delays.…”
Section: Introductionmentioning
confidence: 99%
“…CS is widely recognized as a focal source of AF. The role of CS as the critical driver of AF may be explained by the fact that CS is surrounded by a myocardial sleeve, fibers from which connect to the left atrial myocardium along the inferior mitral annulus, providing the second‐largest electrical continuity between the atria . This CS–LA connection can be the source of recurrence after AF ablation .…”
Section: Discussionmentioning
confidence: 99%
“…In these locations, there is myocardial tissue that can instigate repetitive firing or in some cases, episodic re-entrant activation of the veins (36). While less common, rapid ectopic activity can also arise from the muscular sleeves of the superior vena cava, coronary sinus or ligament of Marshall (37)(38)(39). The exact mechanisms behind AF initiation due to rapid firing have not been fully elucidated but it may potentially involve enhanced automaticity, micro-reentry, or triggered activity (40).…”
Section: Pathophysiologymentioning
confidence: 99%